Caracterización de la población migrante del Perú en relación al empleo, durante el quinquenio 2021 - 2017 - Saboya Torrejón, Ursula (2021)
This research focuses on the study of the internal migration of the country, which consists of the transfer of people from the place of birth to another where they have resided for at least five years. This master thesis seeks to determine the characterization of the migrant population of Peru in relation to employment, during the five-year period 2012 - 2017. With this objective, the present investigation of Quantitative type, Descriptive level and Non-Experimental design was carried out. The research concludes that the migrant population of Peru is characterized by having an employment relationship considered as a Dependent worker (75.41%), and is developed mainly in the Services activity (39.40%), contrary to what was stated in the general hypothesis that it considered that they worked independently and in the Commerce sector. The classification of the migrant population of working age according to the condition of the work activity, has in first place the Economically Active Employed Population with 819,730 people, which is equivalent to 62.72% of the total. In this same aspect, the age analysis of the migrant population shows a high concentration in the range 20-24 Years with 238,972 people, which means 16.67%. This young population migrates not only in search of better job opportunities, but also in search of a better educational offer. The educational level is mostly Secondary with 574,778 people (40.10%).